2014
DOI: 10.1016/j.nuclphysa.2014.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of collective behavior in small systems

Abstract: We perform 3+1D viscous hydrodynamics calculations of proton-nucleus (pA) and nucleus-nucleus (AA) collisions. Our goal is to understand the apparent collective behavior recently observed in pA collisions and to verify whether the highest multiplicity collision systems can be accurately described as a relativistic fluid. We compare our calculations of flow variables to existing measurements, and demonstrate that hydrodynamics correctly captures the measured trends. We show that our predictions for the pair cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 37 publications
(33 reference statements)
2
41
1
Order By: Relevance
“…Reasons for this could be the neglected initial state correlations and/or the lack of a detailed description of the fluctuating subnucleonic structure of the proton. Our results for p+A collisions differ significantly from those in [28,29,30,31], suggesting that the details of the initial shape in small systems are of paramount importance. 3 We predict an increase of both v 3 and v 5 in 3 He+Au collisions compared to d+Au collisions, while the even harmonics are comparable in both systems.…”
Section: Discussioncontrasting
confidence: 82%
“…Reasons for this could be the neglected initial state correlations and/or the lack of a detailed description of the fluctuating subnucleonic structure of the proton. Our results for p+A collisions differ significantly from those in [28,29,30,31], suggesting that the details of the initial shape in small systems are of paramount importance. 3 We predict an increase of both v 3 and v 5 in 3 He+Au collisions compared to d+Au collisions, while the even harmonics are comparable in both systems.…”
Section: Discussioncontrasting
confidence: 82%
“…Meanwhile, figure 13 shows that for v 2 {2}/v 2 [2] the agreement between data and DPMJET is better in low multiplicity p-Pb collisions, where no evidence of anisotropic collectivity is achieved from previous measurements [36,38]. In addition, the hydrodynamic calculations [62] from MUSIC v2.0 using a modified MC-Glauber initial state and η/s = 0.08 are also presented in figures 12 and 13. These calculations in general underpredict the measured v 2 coefficients but agree better with the data in high multiplicity than in low multiplicity classes.…”
Section: Pb-pb Collisionsmentioning
confidence: 87%
“…Neither the DPMJET model, which does not incorporate anisotropic flow, DPMJET calculations are presented by pink shaded areas. Hydrodynamic calculations (MUSIC) with modified MC-Glauber initial conditions and η/s = 0.08 are shown as magenta lines [62]. nor the hydrodynamic model, which does not include non-flow contributions, could provide a quantitative description of the data.…”
Section: Discussionmentioning
confidence: 99%
“…The study of these collisions at the Relativistic Heavy Ion Collider (RHIC) and at the Large Hadron Collider (LHC) has demonstrated that matter at temperatures above the crossover between hot hadronic matter and hotter QGP exhibits strong collective phenomena [1][2][3][4][5][6][7] which can be described successfully by hydrodynamic simulations of the rapid expansion and cooling of the initially lumpy droplets of matter produced in the collisions [8][9][10][11][12][13][14][15][16][17][18]. Such strong collectivity has also recently been observed in smaller colliding systems, including p-Pb, p-p or 3 He-Au [19][20][21][22][23][24][25][26][27][28][29], for which hydrodynamic simulations also seem to be successful [30][31][32][33][34][35][36][37]. The applicability of hydrodynamics from early times in the evolution and for small systems suggests that the matter formed in these ultrarelativistic collisions is a strongly coupled liquid.…”
Section: Introductionmentioning
confidence: 99%